Cobalt‐Doping in Molybdenum‐Carbide Nanowires Toward Efficient Electrocatalytic Hydrogen Evolution. (18th May 2016) - Lin, Huanlei; Liu, Ning; Shi, Zhangping; Guo, Yulin; Tang, Yi; Gao, Qingsheng
Abstract : Efficient hydrogen evolution reaction (HER) over noble‐metal‐free electrocatalysts provides one of the most promising pathways to face the energy crisis. Herein, facile cobalt‐doping based on Co‐modified MoO x –amine precursors is developed to optimize the electrochemical HER over Mo2 C nanowires. The effective Co‐doping into Mo2 C crystal structure increases the electron density around Fermi level, resulting in the reduced strength of Mo–H for facilitated HER kinetics. As expected, the Co‐Mo2 C nanowires with an optimal Co/Mo ratio of 0.020 display a low overpotential ( η 10 = 140 and 118 mV for reaching a current density of –10 mA cm −2 ; η 100 = 200 and 195 mV for reaching a current density of –100 mA cm −2 ), a small Tafel slope (39 and 44 mV dec −1 ), and a low onset overpotential (40 and 25 mV) in 0.5m H2 SO4 and 1.0m KOH, respectively. This work highlights a feasible strategy to explore efficient electrocatalysts via engineering on composition and nanostructure. Abstract : Cobalt‐doping into Mo2 C increases the electron density of Mo and optimizes the electrocatalytic hydrogen evolution over Mo2 C nanowires. With an optimal Co/Mo ratio, the Co‐Mo2 C nanowires exhibit high activity and good stability in both acidic and basic electrolytes, performing among the best of current noble‐metal‐free electrocatalysts.